Effect of Plain Versus Sugar‐Sweetened Breakfast on Energy Balance and Metabolic Health: A Randomized Crossover Trial. Issue 4 (28th February 2020) - Carroll, Harriet A.; Chen, Yung‐Chih; Templeman, Iain S.; Wharton, Phoebe; Reeves, Sue; Trim, William V.; Chowdhury, Enhad A.; Brunstrom, Jeff M.; Rogers, Peter J.; Thompson, Dylan; James, Lewis J.; Johnson, Laura; et al.
Abstract : Objective: This study investigated the effect of 3 weeks of high‐sugar ("Sweet") versus low‐sugar ("Plain") breakfast on energy balance, metabolic health, and appetite. Methods: A total of 29 healthy adults (22 women) completed this randomized crossover study. Participants had pre‐ and postintervention appetite, health, and body mass outcomes measured, and they recorded diet, appetite (visual analogue scales), and physical activity for 8 days during each intervention. Interventions were 3 weeks of isoenergetic Sweet (30% by weight added sugar; average 32 g of sugar) versus Plain (no added sugar; average 8 g of sugar) porridge‐based breakfasts. Results: Pre‐ to postintervention changes in body mass were similar between Plain (Δ 0.1 kg; 95% CI: −0.3 to 0.5 kg) and Sweet (Δ 0.2 kg; 95% CI: −0.2 to 0.5 kg), as were pre‐ to postintervention changes for biomarkers of health (all P  ≥ 0.101) and psychological appetite (all P  ≥ 0.152). Energy, fat, and protein intake was not statistically different between conditions. Total carbohydrate intake was higher during Sweet (287 ± 82 g/d vs. 256 ± 73 g/d; P  = 0.009), driven more by higher sugar intake at breakfast (116 ± 46 g/d vs. 88 ± 38 g/d; P  < 0.001) than post‐breakfast sugar intake (Sweet 84 ± 42 g/d vs. Plain 80 ± 37 g/d; P  = 0.552). Participants reported reduced sweet desire immediately after Sweet but not Plain breakfasts (trial × time P  < 0.001). Conclusions: Energy balance, health markers, and appetite did not respond differently to 3 weeks of high‐ or low‐sugar breakfasts.